Pengaruh Disiplin Kerja Dan Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat Pada Kantor Kecamatan Bungah Kabupaten Gresik - Muhammad Imron Hamzah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This research aims to find out whether work discipline and quality of public services influence public satisfaction at the Bungah sub-district office, Gresik district. This research uses primary data by distributing questionnaires to all employees. The population used is people who provide services at the Bungah sub-district office. The analysis technique used is multiple linear regression analysis. The results obtained are that work discipline has a positive and significant effect on community satisfaction at the Bungah sub-district office, Gresik district. and service quality has a positive and significant effect on community satisfaction at the Bungah District office, Gresik Regency.